Chronic inflammation: A key role in degeneration of bicuspid aortic valve. (May 2019) - Manno, G.; Bentivegna, R.; Morreale, P.; Nobile, D.; Santangelo, A.; Novo, S.; Novo, G.
Abstract: Introduction: Bicuspid aortic valve (BAV) is the most common congenital valvular heart defect resulting from abnormal aortic cusp formation during heart development, where two of the three normal and equal sized cusps fuse into a single large cusp resulting in a two cusps aortic valve. Over the past years, much interest has been given in understanding the pathogenesis of BAV and its complications. In this review, we focused on the role of inflammation, involved in the degeneration of BAV and the development of its complications. Role of inflammation: From a pathophysiological point of view, BAV may rapidly progress into aortic stenosis (AS) and is related to aortopathy. Several histopathologic studies have demonstrated that the development and progression of alterations in bicuspid aortic valve are related to an active process that includes: oxidative stress, shear stress, endothelial dysfunction, disorganized tissue architecture, inflammatory cells and cytokines. These factors are closely related one to each other, constituting the basis of the structural and functional alterations of the BAV. Conclusion: Chronic inflammation plays a key role in the degeneration of BAV. Severe aortic stenosis in bicuspid aortic valves is associated with a more aggressive inflammatory process, increased inflammatory cells infiltration and neovascularization when compared to tricuspid AS. These findings might help to explain the more frequent onset and rapid progression of AS and the heavy aortic valve calcification seen in patients with BAV. Highlights: Bicuspid aortic valve (BAV) is the most common congenital valvular heart. Over the past years, much interest has been reached in understanding the pathogenesis of BAV and its complications. Inflammation play a key role in pathogenesis of BAV alterations.